A Pathological Analysis of Canaliculitis Concretions: More Than Just Actinomyces - Balaji Perumal; John Andrew Carlson; Dale Robert Meyer (Scientifica)
Purpose. Canaliculitis is classically associated with Actinomyces species, which are filamentous bacteria; the purpose of this study was to evaluate the extent to which nonfilamentous bacteria colonize canalicular concretions by using graded histopathological analysis. Methods. This is a series of 16 cases. The percentage of Gram-positive/Gomori’s methenamine silver-positive filamentous bacteria (Actinomyces) versus the total bacteria identified was graded, and the types of bacteria seen were recorded. Nonfilamentous bacteria were categorized based upon Gram stain (positive or negative) and morphology (cocci or rods). Results. There were 11 females and 5 males. Nonfilamentous bacteria were identified in 16 of 16 (100%) specimens and filamentous bacteria were identified in 15 of 16 (94%) specimens. The mean percentage of filamentous bacteria relative to total bacteria was 57%. Regarding the nonfilamentous bacteria present, 69% of specimens had Gram-positive cocci only, 25% had Gram-positive and Gram-negative cocci, and 6% had Gram-positive cocci and Gram-positive rods. Conclusion. In the current study, there was a mix of filamentous and nonfilamentous bacteria in almost all canalicular concretions analyzed. Nonfilamentous bacteria may contribute to the pathogenesis of canaliculitis. In addition, the success of bacterial culture can be variable; therefore, pathological analysis can assist in determining the etiology.